2022
DOI: 10.5005/jp-journals-10071-23920
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Immature Granulocyte Count as the Earliest Biomarker for Sepsis

Abstract: Background Diagnosing sepsis early is important for its successful management. Various biomarkers are being used currently, but mostly they are either expensive or not readily available. This study aims to evaluate usefulness of automated immature granulocyte count (IG#) and immature granulocyte percentage (IG%) as early diagnostic markers of sepsis and compares it to other established predictive markers. Patients and methods In this prospective observational study, 137… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…A [10]. Similarly, receiver operating characteristic curves in our study showed that IGC and IG% are better predictors of infection with AUC of 0.75 and 0.79, respectively.…”
Section: Discussionsupporting
confidence: 74%
“…A [10]. Similarly, receiver operating characteristic curves in our study showed that IGC and IG% are better predictors of infection with AUC of 0.75 and 0.79, respectively.…”
Section: Discussionsupporting
confidence: 74%
“…Van der Geest et al 4 found the optimal IG% cutoff to identify infection to be 0.4%. And Bhansaly et al 1 reported an optimal IG% cutoff as low as 0.7% to prospectively predict sepsis within 24 hours with AUC of 0.818. Ideally, we should evaluate IG misclassification in similarly low IG% levels.…”
Section: Discussionmentioning
confidence: 99%
“…However, these findings are limited to our smear practice and patient population and NEUT‐RI may thus be of significant value in other laboratory settings for identification of misclassified results. Also, considerations should be made to whether NEUT‐RI values ≥56 or the presence of the Abnormal WBC scattergram flag should affect the release of the preliminary Sysmex result prior to the completion of the smear analysis, as crucial clinical decisions regarding infection status and sepsis may be made in the meantime 1–4,7 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One such biomarker that has shown promise in the diagnosis and prognosis of EC is delta neutrophil index (DNI) (8,9). DNI is a laboratory parameter that measures the difference between the fraction of immature granulocytes and mature granulocytes in the bloodstream (8)(9)(10). DNI is a sensitive marker of systemic inflammation and infection and has been shown to be a promising prognostic biomarker in various cancers, including EC (10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%